The Influence of Green Ambidexterity Innovation, Strategic Stakeholder Alliance, and Green HRM Practices on Sustainable Green Competitive Advantage and Sustainable Business Performance of SMEs - Zainurrafiqi Zainurrafiqi; Isnain Bustaram; Istianah Asas; Moh. Redy; Ummi Wahyuni; Arikatul Faradies; Amanatus Sholehah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study investigates the influence of Green Ambidexterity Innovation (GAI), Strategic Stakeholder Alliance (SSA), and Green Human Resource Management Practices (GHRMP) on Sustainable Green Competitive Advantage (SGCA) and Sustainable Business Performance (SBP) in Small and Medium Enterprises (SMEs) in Pamekasan, Indonesia. With increasing global competition and the need for environmentally sustainable practices, SMEs face the challenge of balancing innovation, stakeholder collaboration, and environmental responsibility. Using a mixed-method approach, this research employs both quantitative surveys of 100 SME managers and qualitative interviews to gather comprehensive data. Quantitative data analysis is conducted through WarpPLS 7.0, focusing on both the inner and outer models of the relationships among variables. Findings indicate that Green HRM Practices significantly positively impact SGCA, while Green Ambidexterity Innovation and Strategic Stakeholder Alliances demonstrate weaker or insignificant effects on SGCA. Moreover, SGCA does not significantly influence SBP. These results suggest that while Green HRM Practices can enhance competitive advantage, a more nuanced approach may be required for SMEs to fully leverage innovation and stakeholder collaboration for long-term sustainable business performance. This research contributes to the growing body of knowledge on green strategies in SMEs, offering practical recommendations for business leaders to integrate sustainability into their operational strategies. The study aligns with Sustainable Development Goals (SDG) 8, 9, 12, and 13, aiming for responsible production and climate action.